2022
DOI: 10.1073/pnas.2120808119
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation in the subthalamic nucleus for Parkinson’s disease can restore dynamics of striatal networks

Abstract: Significance Deep brain stimulation (DBS) in the subthalamic nucleus (STN) is highly effective for treating the motor symptoms of Parkinson’s disease (PD). However, the neural mechanisms by which DBS acts are unknown. PD symptoms are tied to altered brain rhythms in basal ganglia (BG) and particularly the striatum. We develop a biophysical model of a BG neural pathway and show how beta oscillations can emerge throughout BG in PD. We then establish a mechanism by which DBS in STN can interrupt these a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 150 publications
(384 reference statements)
2
14
0
Order By: Relevance
“…Further limitations of our model include the lack of dynamics to account for plasticity effects, and the fact that selecting an adaptive integrate and fire neuron model we did not take into account specific currents that are included in Hodgkin and Huxley models of basal ganglia (e.g. [ 89 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Further limitations of our model include the lack of dynamics to account for plasticity effects, and the fact that selecting an adaptive integrate and fire neuron model we did not take into account specific currents that are included in Hodgkin and Huxley models of basal ganglia (e.g. [ 89 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Because the recording site was >1.3 mm upstream of the stimulation site, the excitation induced at the efferent axons by the stimulation should have propagated antidromically along the axons to close to the INs in the recording site before activating the INs through axon branches (see the pathway denoted by the orange curve in Figure 1 a). The experiment provides a new method to investigate the antidromic activations of efferent fibers on the local INs rather than the orthodromic activations of afferent fibers, as in previous studies [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The action potential induced by a pulse on the axonal membrane can simultaneously propagate along the axon in two directions: orthodromic propagation to the axonal terminals and antidromic propagation to the neuronal soma [ 9 ]. Studies have shown that through orthodromic propagations, HFS at afferent axons can increase the firing of the postsynaptic neurons (including the interneurons of feedforward circuits) in the downstream area of the stimulation site via synaptic transmissions at axonal terminals [ 14 , 15 , 16 ]. However, it is not clear yet whether the HFS-induced excitation at efferent axons can activate the interneurons of local feedback circuits in the upstream area of the stimulation site through antidromic propagations (see Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics and structure of neuronal networks can be manipulated by stimulation 35 , 37 , 43 , 54 , 73 83 . We use an anti-kindling coordinated reset (CR) stimulation to desynchronize initially synchronized networks.…”
Section: Methodsmentioning
confidence: 99%